2018
DOI: 10.1111/iej.13006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of central administration of alpha‐pinene on capsaicin‐induced dental pulp nociception

Abstract: Pinene exhibited significant curable effects on capsaicin-induced pulpal nociception and inflammation mainly via pharmacological interfacing with GABA and μ-opioid receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 41 publications
(42 reference statements)
1
21
0
Order By: Relevance
“…The impact of α-pinene on pulpal pain in Wistar mice was investigated [78]. Selected mice were cannulated by their lateral ventricles for capsaicin (100 µg) supplementation.…”
Section: Preclinical Pharmacological Activities Of α- and β-Pinenementioning
confidence: 99%
“…The impact of α-pinene on pulpal pain in Wistar mice was investigated [78]. Selected mice were cannulated by their lateral ventricles for capsaicin (100 µg) supplementation.…”
Section: Preclinical Pharmacological Activities Of α- and β-Pinenementioning
confidence: 99%
“…Superoxide dismutase, catalase, peroxidase, NO, IL-6 [155] C57BL/6 mice CD4, CD8 and NK cells [102] Wistar rats COX2 [156]…”
Section: Anti-inflammatory Antioxidantmentioning
confidence: 99%
“…Sprague-Dawley rats Sleep rhythm [157] Mice BDNF, TH, EPM test [158] ICR and C57BL/6N mice GABA BZD receptor, sleep behavior [159] Wistar-Kyoto mice Forced swim test, oxidative phosphorylation expression [160] Wistar rats Sensorimotor severity score [155] C57BL/6 mice Schizophrenia-like behavior [161] Analgesic BALB/c mice Tail-flick test [162] Mice Neuropathic pain [163] Wistar rats Nociception [156] Abbreviations: BDNF, brain-derived neurotrophic factor; BZD, benzodiazepine; EPM, elevated plus maze; ERK, extracellular signal-regulated kinase; GABA, γ-aminobutyric acid; Ig-E, immunoglobulin E; JNK, c-jun N-terminal kinase; MMP-1, metalloproteinase 1; MMP-13, metalloproteinase 13; NF-kB, nuclear factor-B; ROS, reactive oxygen species; TH, tyrosine hydroxylase.…”
Section: Antidepressant Sedativementioning
confidence: 99%
“…In this context, α-pinene exhibited significantly anti-inflammatory and analgesic effects through inhibition of COX-2. Moreover, the analgesic effect of α-pinene on capsaicin-induced pulp nociception was blocked by co-administration with bicuculline or naloxone, thus suggesting that this effect could be mediated, at least in part, by interaction with GABA-A and µ-opioid receptors [163].…”
Section: Alpha (α)-And β-Pinenementioning
confidence: 99%
“…In this sense, another study showed that α-pinene was also able to inhibit human hepatoma tumor progression by inducing G2/M phase cell cycle arrest [162]. Regarding α-pinene antinociceptive effects, it was previously demonstrated its beneficial potential in capsaicin-induced dental pulp nociception [163], xylene-induced ear edema, and formalin-inflamed hind paw models [164]. In this context, α-pinene exhibited significantly anti-inflammatory and analgesic effects through inhibition of COX-2.…”
Section: Alpha (α)-And β-Pinenementioning
confidence: 99%